Critical advances in biofabrication and biomaterial strategies in tracheal tissue engineering: A comprehensive overview - Naik, Sonali S.; Dutta, Naba K.; Nair, Kiran Sukumaran; Choudhury, Namita Roy (Advances in Colloid and Interface Science, 2025)
The trachea is a vital respiratory organ that connects the larynx to the lungs and performs crucial functions. Various conditions can cause severe and often irreversible damage to individuals trachea of all age groups. Tracheal regeneration remains a major challenge in respiratory medicine, requiring a innovative solutions to address various underlying causes. Existing clinical interventions often have significant limitations and associated complications. Tissue engineering has potential, but its effectiveness has been limited due to challenges such as poor durability and insufficient revascularization. This review aims to provide a comprehensive exploration of the landscape of tracheal regeneration, shedding light on the path towards advancements in addressing extensive tracheal defects. It follows a structured approach, introducing various surgical procedures, along with their associated complications. Subsequently, it delves into the myriad biomaterials investigated in the realm of tracheal tissue engineering, emphasizing the significance of design considerations in scaffold fabrication. The review then navigates through various platforms utilized in tracheal tissue engineering and recent innovative approaches employed in this domain. Additionally, it provides insights into the clinical translation of tissueengineered trachea, highlighting recent advancements and challenges encountered in real-world applications. Finally, it discusses the significant challenges and offers a perspective outlook on the future of tracheal tissue engineering. Addressing current limitations and envisioning novel strategies, the review contributes to the ongoing dialogue and progression in this critical field of regenerative medicine.
Keywords: 3D printing; 4D printing; Additive manufacturing; Biomaterials; Cell sheet engineering; Organoid printing; Tracheal tissue engineering

Design, fabrication and comprehensive testing of biodegradable 3D printable hybrid polymer airway splints - Naik, Sonali S.; Vongsvivut, Jitraporn; Dekiwadia, Chaitali; Abraham, Amanda N.; Dutta, Naba K.; Choudhury, Namita Roy; Nair, Kiran Sukumaran (Journal of Materials Chemistry B, 2025)
The trachea plays a critical role in respiration and airway protection but is susceptible to damage from pathological conditions such as stenosis, fistula, obstruction, and malacia. While existing treatment options are useful, they often have limitations, driving the need for innovative alternatives. This study introduces a novel approach using 3D printing technology to create hybrid degradable tracheal splints made of pectin-g-polycaprolactone (pec-g-PCL). We synthesized and characterized various compositions of pec-g-PCL to assess their physicochemical properties and tested their suitability for 3D printing. The resulting materials demonstrated the potential for use as tracheal splints. Using CAD software, we created two distinct designs, which were then fabricated according to those specifications. Micro-computed tomography (micro-CT) imaging revealed splint porosities ranging from 80% to 90%, highlighting their intricate internal microarchitecture. Design verification was conducted through numerical simulations, based on finite element modeling (FEM), to evaluate mechanical properties and computational fluid dynamics (CFD) for assessing the airflow dynamics of the fabricated tracheal splints. Degradation studies indicated that the 3D-printed scaffolds exhibited approximately 30% degradation over a period of 35 days. In vitro, biocompatibility assessments confirmed the scaffold's compatibility with biological systems. These findings demonstrate the potential of pec-g-PCL-based tracheal splints as a promising solution to overcome limitations in current treatments. This research paves the way for advanced biomaterials that could revolutionize patient care by offering more effective solutions for managing tracheal disorders.